Improving Early Childhood Fine Motor Skills Through Planting Microgreens Activities in Group A of Hidayatul Islamiyah Kindergarten - Iis Uswatun Hasanah; Anugrah, Yuwan Fijar (Kiddie: Early Childhood Education and Care Journal, 2024)
Farming activities can teach the value of cooperation, the beauty of nature or the environment as well as character building in children such as discipline, patience and also hard work to get the expected results. Microgreens are vegetables that are harvested when they are still young. Suitable for use in early childhood learning because the process of planting, caring for and harvesting is not difficult for children to do. The activity of planting microgreens can also stimulate the smooth muscles located in the fingers, such as when holding soil or other planting media, spraying plants, and also when picking or cutting leaves and other plant products. This research is classroom action research with data analysis using quantitative descriptive methods which include the planning stage, action stage, observation stage and also reflection. The aim of this research is to determine whether there is an increase in fine motor skills of young children through the activity of planting microgreens in group A of the Hidayatul Islamiyah Kindergarten, Wanayasa district, Purwakarta with research subjects of 11 children. The data collection techniques used are observation and documentation. The results of this research show that the activity of planting microgreens apart from forming the character of discipline, patience, and also hard work to produce something that is expected to also improve children's fine motor skills in various activities. It is hoped that the results of this research can be a reference for educators in choosing fun learning activities to stimulate children's fine motor development. Kegiatan bercocok tanam dapat mengajarkan nilai kerjasama, keindahan alam atau lingkungan serta pembentukan karakter pada anak seperti kedisiplinan, kesabaran dan juga kerja keras untuk mendapatkan hasil yang diharapkan. Microgreens adalah sayuran yang dipanen saat masih muda. Cocok digunakan dalam pembelajaran anak usia dini karena proses menanam, merawat dan memanennya tidak sulit untuk dilakukan oleh anak-anak. Kegiatan menanam microgreens juga dapat menstimulasi otot-otot halus yang terdapat pada jari-jari tangan, seperti pada saat memegang tanah atau media tanam lainnya, menyemprot tanaman, dan juga pada saat memetik atau memotong daun dan hasil tanaman lainnya. Penelitian ini merupakan penelitian tindakan kelas dengan analisis data menggunakan metode deskriptif kuantitatif yang meliputi tahap perencanaan, tahap tindakan, tahap observasi dan juga refleksi. Tujuan dari penelitian ini adalah untuk mengetahui apakah terdapat peningkatan kemampuan motorik halus anak usia dini melalui kegiatan menanam microgreens di kelompok A TK Hidayatul Islamiyah Kecamatan Wanayasa, Purwakarta dengan subjek penelitian sebanyak 11 anak. Teknik pengumpulan data yang digunakan adalah observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwa kegiatan menanam microgreens selain membentuk karakter disiplin, sabar, dan juga kerja keras untuk menghasilkan sesuatu yang diharapkan juga dapat meningkatkan kemampuan motorik halus anak dalam berbagai kegiatan. Diharapkan hasil penelitian ini dapat menjadi referensi bagi para pendidik dalam memilih kegiatan belajar yang menyenangkan untuk menstimulasi perkembangan motorik halus anak.